Measuring Organization Culture in Different Organizations - An Empirical Study - Rana, Geeta; Garg, Pooja (Prabandhan: Indian Journal of Management, 2011)
The purpose of this paper is an attempt to determine the organization culture of managers working in public and private organizations. The sample of the study comprised of total 100 managers from BHEL (n=63), a public sector organization and DABAR India Ltd. (n=37), a private sector organization. A standardized questionnaire was used, comprising of 40 items, developed by the Udai Pareek. The results of the study revealed that on dimensions of organization culture like openness, confrontation, trust, authenticity, proaction, autonomy, collaboration and experimentation, the score of managers from two organizations did not differ significantly. In order to draw broader conclusions, it was necessary to explore alternative explanations and conduct further empirical research in other industries. Multinationals interested in developing industry in India could benefit from information given in this paper about the organization culture and its different work related aspect. This study contributed to the understanding of factors influencing culture in public and private organizations.